2016
DOI: 10.1186/s12889-016-3577-9
|View full text |Cite|
|
Sign up to set email alerts
|

Trend of determinants of birth interval dynamics in Bangladesh

Abstract: BackgroundThe distribution of birth intervals can be used to draw attention to important characteristics of dynamics of fertility process. The main objective of this paper is to examine the effects of socioeconomic, demographic and proximate determinants on the length of birth intervals of women of Bangladesh and also to see whether the effects are changed over the years.MethodsBirth intervals can be considered as correlated time-to-event data because two or more birth intervals could correspond to a single mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 22 publications
(34 reference statements)
9
56
1
Order By: Relevance
“…The current study indicates that couples who were satisfied with their economic status tended to have longer pregnancy spacing. This result is in accordance with the result of the study that showed low income families tended to have more children with shorter pregnancy spacing [ 25 ]. This might be because the families with higher economic status usually had higher education status, too.…”
Section: Discussionsupporting
confidence: 92%
“…The current study indicates that couples who were satisfied with their economic status tended to have longer pregnancy spacing. This result is in accordance with the result of the study that showed low income families tended to have more children with shorter pregnancy spacing [ 25 ]. This might be because the families with higher economic status usually had higher education status, too.…”
Section: Discussionsupporting
confidence: 92%
“…That means birth intervals are considered as time-to-event data. Among the important covariates for modeling birth intervals that were reported in earlier studies (Khan et al, 2016;Mahmood et al, 2013;Chakraborty et al, 1996), those available in BDHS data were selected for this study. Web- Table 14.1 describes summary statistics of the covariates under consideration.…”
Section: Empirical Data Analysis: Determining the Birth Interval Dynamentioning
confidence: 99%
“…However, these software implementations of frailty models differ with respect to types of regression models used (e.g., parametric and semiparametric), the assumed base-line hazard and frailty distributions for the estimation of the respective parameters as well as the optimization technique. In real-life applications, where true baseline hazard and frailty distributions are generally unknown, the choice of a parametric or a non-parametric baseline hazard function, as well as the assumed frailty distributions in the frailty model, is rather arbitrary (Khan et al, 2016;Mahmood et al, 2013). The ramifications of the potential violation of this assumption on the parameters associated with the survival model covariates ( 's) and frailties (✓) are hard to assess empirically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the processing of this article [ 1 ], the following typographical error occurred on page 3: , ui was incorrectly introduced:…”
Section: Erratummentioning
confidence: 99%